Pelatihan Peningkatan Kualitas Produksi dan Pemasaran Makanan Paket Eungkout Keumamah Pada Industri Rumahan Lhokseumawe Dalam Mendukung SDGS-3 Good Health and Well Being - Endang Syahriani; Yusuf A Samad; Dina Hendiani; Sutoyo; Chairul Bariah (LPPM Universitas Almuslim, 2023)
This service activity aims to increase the understanding and ability of prospective home industry entrepreneurs to produce quality production and marketing that is in accordance with input-output. Another aim is to develop synergy between universities and home industry business actors so that training and assistance is needed in forming and developing strategies that work well and are in accordance with knowledge based on empirical studies. The material presented is the concept of improving production quality, up to date marketing techniques. The results of this service can be used as input for lecturers and educational staff to increase professionalism and also as input in preparing teaching materials for managerial economics and industrial economics.